Parallax and the summum bonum: a modal resolution for the problem of the constitution of the Highest Good - Salgado Maia, Francisco (Con-Textos Kantianos. International Journal of Philosophy, 2024)
Kant establishes as the ultimate object of practical reason that which he calls summum bonum – the absolute teleological determination which is constituted by the realization of a kingdom of ends in which happiness is distributed in proportion with the morality of agents. This connection between happiness and morality must raise a fundamental objection with those familiar with Kant’s deontology: how can morality, which must remain autonomous and self-sufficient, be necessarily linked with the happiness which the Kantian moral doctrine só disdains? In this article, we will examine the constitutive elements found in the deduction of the highest good, we will attempt to assess any possible flaws in Kant’s doctrine regarding this object, and provide a new understanding for the connection between morality and happiness within the highest good, through the concepts of parallax and perspective modality.